Integrating Islamic Values and Technology Ethics into Digital Learning in the Society 5.0 Era - Hamada, Muhammad Yusuf; Sunardi, Syahlani; Jafar, Sadik; Karim, Rahman A. (Ahlussunnah: Journal of Islamic Education, 2026)
The rapid advancement of digital technology in education has created significant opportunities for learning innovation while simultaneously raising ethical challenges that may weaken the integration of moral and spiritual values in educational practices. This study aims to analyze the integration of Islamic values and ethical principles in educational technology and to develop a conceptual framework relevant to education in the Society 5.0 era. A qualitative approach was employed using content analysis of scholarly publications and academic sources published between 2018 and 2026. The data were analyzed through categorization, interpretation, and thematic synthesis to identify the relationships among Islamic values, technology ethics, and digital learning. The findings reveal that the integration of Islamic values and ethics in educational technology is constructed through three main dimensions: philosophical foundations, ethical technology governance, and pedagogical implementation. The values of tawhid, amanah, honesty, and ihsan serve as the foundation for developing humanistic educational technologies, while the principles of responsibility, justice, and public benefit guide the ethical use of digital technologies. This study proposes an integrative framework that connects technological, ethical, and pedagogical dimensions to support learning that promotes not only academic achievement but also character and spiritual development. These findings contribute to the development of value-oriented educational technology in the Society 5.0 era.